(3TQM bhdg Udi Gddg Ydjg hSde SHYI jXdge aj Xd YQTgs - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
(3hHYO agPG TQM Ydi MOjK CHj gQjQI Yf GdfHi Udi Gddg Ydjg hSde bGd SHYI jXdge Gddg ai Xdg jhe dG Xd EdG Xdg EeGe YGOd hTGH fTC ai YHGOI Gddg hQLd bdHg eYdb HGdeSLO EPG NQL efg MJi jYhO Edjg s
(3BNQgG (B:s
(3hYGedkG HWGYI Gddg cGdYGOd GdYGHO GdPcQ hGdYWGA s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B291s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI s
Keywords: (3GdMOjK h GdeUWdMs